1998
DOI: 10.1182/blood.v91.10.3935.3935_3935_3942
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of CD95 (Fas/Apo-1) Gene in Adult T-Cell Leukemia Cells

Abstract: CD95 antigen (also known as Fas or Apo-1) and Fas ligand play key roles in apoptosis of cells of the immune system, function as effector molecules of cytotoxic T lymphocytes, and function in the elimination of activated lymphocytes during the downregulation of the immune response. The critical roles of the Fas-Fas ligand system in apoptosis suggest that its inactivation may be involved in malignant transformation. We analyzed the expression of Fas antigen on adult T-cell leukemia (ATL) cells by flow cytometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
4
27
1
Order By: Relevance
“…In the present study, results revealed that CD 95 % in blood of newly diagnosed ALL cases is significantly low when compared to controls while after treatment it showed significant increase. Consistent with our results, Tamiya et al [146] found defects in expression of Fas antigen on leukemia cells due to mutations in Fas genes of these cells. Moreover, Muschen et al [147] revealed that CD 95 /Fas (receptor-ligand system), is mutated and downregulated in lymphoid and solid tumors and loss of its function is associated with resistance to drug induced cell death.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, results revealed that CD 95 % in blood of newly diagnosed ALL cases is significantly low when compared to controls while after treatment it showed significant increase. Consistent with our results, Tamiya et al [146] found defects in expression of Fas antigen on leukemia cells due to mutations in Fas genes of these cells. Moreover, Muschen et al [147] revealed that CD 95 /Fas (receptor-ligand system), is mutated and downregulated in lymphoid and solid tumors and loss of its function is associated with resistance to drug induced cell death.…”
Section: Discussionsupporting
confidence: 93%
“…These germ‐line mutation models indicate that the key role of the Fas/FasL system is maintaining immune homeostasis. In agreement with these, human lymphoid malignancies were reported to have somatic mutations of the Fas gene (10–12).…”
mentioning
confidence: 61%
“…We speculate that Tax plays an important role for HTLV‐I‐infected cells to persistently proliferate and to escape Fas‐mediated apoptosis during the acute and carrier states, and then genetic and epigenetic changes accumulate in the host genome mediated by a mutator phenotype of Tax, which finally leads to Tax‐independent proliferation and survival of HTLV‐I‐infected T‐cells. Interestingly, 2–5% of ATL cells were reported to exhibit mutations in the Fas gene with associated Fas‐negative phenotype (Tamiya et al . 1998).…”
Section: Discussionmentioning
confidence: 99%